Michelena in El cojo ilustrado (Mayéutica Revista Científica de Humanidades y Artes, 2022)
We present some drawings by the Venezuelan painter Arturo Michelena published in the cultural magazine El Cojo Ilustrado between 1892 and 1898. Michelena is the first Venezuelan artist to obtain recognition at the Salon of the Society of French Artists in Paris with his work El niño enfermo (1887), with which he obtains the Second Class Medal and the Hors concours, the highest distinction for a foreign artist.
Keywords: Arturo Michelena; El Cojo Ilustrado; Venezuelan art; XIX century